PENGARUH KEBIJAKAN DIVIDEN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN MANUFAKTUR SUB-SEKTOR KOSMETIK YANG TERDAFTAR DI BEI PERIODE 2016-2020 - Deasy Femayona Devi (Bisnis-Net, 2023)
ABSTRACT The purpose of this study was to determine the effect of dividend policy and firm sizeon firm value in the cosmetic sub-sector manufacturing companies listed on theIndonesia Stock Exchange for the 2016-2020 period.The method used in this study is aÂ quantitative method. The sample used in this study were 6 companies. The samplingtechnique used is purposive sampling. Sources of data used in this study is secondarydata. Data analysis was performed using SPSS Version 23.The results of this studyreveal that 1) dividend policy does not have a significant positive effect on firm valuein the right cosmetics sub-sector manufacturing company as evidenced by tcount of0.179 (0.179 < 3.183) and a significance value of 0.859 (0.859 > 0.05). 2) companysize has a negative effect on firm value in the cosmetics sub-sector manufacturingcompany, this is evidenced by tcount -2,909 (-2,909 < 3.184) and a significance valueof 0.007 (0.007 < 0.05). 3) dividend policy and firm size have a positive influence onfirm value in the cosmetic sub-sector manufacturing companies, this is evidenced byfcount of 4.280 (4.280 < 6.94) and a significance value of 0.24 (0.24 > 0.05) .Keywords: Dividen Policy;Company Size;Company Value.